Profitability and systematic trading - Harris, Michael (John Wiley, 2008)
n order to overcome certain obstacles and make more informed decisions in today’s markets, you need to use the appropriate models and apply careful analysis. Nobody understands this better than author Michael Harris. And now, with Profitability and Systematic Trading, he reveals how to achieve this goal, by discussing some of the most important trading concepts he’s worked on during twenty years of research and development in this field